Tree-ring analysis: biological, methodological, and environmental aspects / (Acc: 2336) - Wimmer, R. (Rupert); Vetter, Roland E. (Wallingford, Oxon, UK ; New York, NY, USA : CABI Pub., 1999)
"Presents 19 chapters discussing recent advances in the biology of tree-ring analysis. The papers result from a 1997 conference sponsored by the International Union of Forestry Research Organizations. They are divided into five sections devoted to the analysis of radial growth processes, anatomical and structural features, historical analysis, environmental interactions, and a section focusing on tropical trees. Some specific topics include a mechanistic cambium activity model, climactic influences in the tropics, the periodicity of cambial growth, and applications in forest monitoring."--SciTech Book News
Keywords: Dendrochronology; Tree-rings.; Trees; Forest ecology